ANALYSIS OF ANTIOXIDANT COMPOUNDS ON PUMPKIN (Cucurbita pepo L.) SEED OIL - Abdillah, Muhammad Nur (Journal of Pharmacopolium, 2018)
Pumpking seed oil (Cucurbita pepo L.) popular as healthy oil and became natural antioxidant as consist of various unsaturated fatty acid, carotenoid, flavonoid and polyphenolic. The purpose of this research is to study the compounds on pumpkin seed oil that has antioxidant activity by determining fatty acids composition of the oil using gas chromatography-mass spectrometry (GC-MS) and antioxidant activity by inhibiting free-radical DPPH and determination of total polypheolic content as gallic acid using UV-Vis spectrophotometry. Pumpkin seed oil was produced by solvent extraction with Soxhlet apparatus used as sample. Oil samples was reacted to form fatty acid methyl ester for component analysis by GC-MS determination. Antifree-redical activity was determined using UV-Vis spectrophotometry to count the IC50 value of concentration series of mixed samples and free-radical DPPH compared to vitamin C as standard antioxidant. Total poliphenolic content as gallic acid was determined using UV-Vis Spectrophotometry by reacting samples with Folin-Ciocalteau reagent. Pumpkin seed oil content at least 10 moderate chain fatty acid, saturated and unsaturated, volatile oil and carotenoid. Antixidant activity of pumpkin seed oil with IC50 value of 16,90(Â±0,28)mg/L in inhibiting free-radical DPPH and has total polyphenolic content as gallic acid of 0,212%.Keywords: pumpkin seed oil, antioxydant, DPPH free radical, polyphenolic, UV sepctrophotometry, GC-MS.